Clinical and immunological research of qualities of antimicrobial disepidermic cryolyophylized xenoderm grafts - Serhii Nazarchuk; Anatolii Sukhodolia; Oleksandr Nazarchuk (Kazimierz Wielki University, 2015)
Nazarchuk Serhii, Sukhodolia Anatolii, Nazarchuk Oleksandr. Clinical and immunological research of qualities of antimicrobial disepidermic cryolyophylized xenoderm grafts. Journal of Education, Health and Sport. 2015;5(8):434-442. ISSN 2391-8306. DOI10.5281/zenodo.31322 http://dx.doi.org/10.5281/zenodo.31322 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A434-442 https://pbn.nauka.gov.pl/works/632549 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 24.09.2015.   UDC: 616+615.47.014.47-616.5-089-74   CLINICAL AND IMMUNOLOGICAL RESEARCH OF QUALITIES OF ANTIMICROBIAL DISEPIDERMIC CRYOLYOPHYLIZED XENODERM GRAFTS   Serhii Nazarchuk1, Anatolii Sukhodolia2, Oleksandr Nazarchuk3   1Khmelnytskyi Regional Clinical Oncological Dispensary, Department of Abdominal Surgery 2Vinnytsya National Pirogov Memorial Medical University, Department of Surgery of the Faculty of Postgraduate Study 3Vinnytsya National Pirogov Memorial Medical University, Department of Microbiology, Virology and Immunology Abstract In the article the results of the research of immunological changes after the using of antimicrobial disepidermic cryolyophilized xenoderm grafts in the model of intestinal anastomosis forming; clinical effectiveness of their use for prevention intestinal sutures' and anastomosis' insolvency in patients with oncological pathology are presented. In experiment, it is shown, that while using DCXG the essential changes of local immune reactivity have place. It is proved  that  the tendency of unevenly and not proportionally increasing of cells with main classes Ig A, Ig M, Ig G, Ig E shows highly active and non-stable local immunologic reactions of intestinal mucosa on using DCXG; the intensity of local immune reactions significantly decreases by the 25th day and is nearby to normal ones. DCXG were used in 50 patients, who underwent surgery in Khmelnytskyi Regional Clinical Oncological Dispensary and Khmelnytskyi Regional Clinical Hospital in 2009-2013 years. The incidence of purulent-inflammatory complications of intestinal anastomosis' insolvency in the main group of patients was above 4,3 % and 16 % in control one. Key words: sutures' insolvency, anastomosis, xenoderm grafts, antimicrobial materials.